An enzyme activation network reveals extensive regulatory crosstalk between metabolic pathways - Sultana Mohammed Al Zubaidi; Muhammad Ibtisam Nasar; Richard A Notebaart; Markus Ralser; Mohammad Tauqeer Alam (Molecular Systems Biology)
Abstract Enzyme activation by cellular metabolites plays a pivotal role in regulating metabolic processes. Nevertheless, our comprehension of such activation events on a global network scale remains incomplete. In this study, we conducted a comprehensive investigation into the optimization of cell-intrinsic activation interactions using Saccharomyces cerevisiae metabolic network as the basis of the analysis. To achieve this, we integrated a genome-scale metabolic model with cross-species enzyme kinetic data sourced from the BRENDA database, and to use this model as a basis to estimate the distribution of enzyme activators throughout the cellular network. Our findings indicate that the vast majority of biochemical pathways encompass enzyme activators, frequently originating from disparate pathways, thus revealing extensive regulatory crosstalk between metabolic pathways. Notably, activators have short pathway lengths, indicating they are activated quickly upon nutrient shifts, and in most instances, these activators target key enzymatic reactions to facilitate downstream metabolic processes. Interestingly, highly activated enzymes are substantially enriched with non-essential enzymes compared to their essential counterparts. This observation suggests that cells employ enzyme activators to finely regulate secondary metabolic pathways that are only required under specific conditions. Conversely, the activator metabolites themselves are more likely to be essential components, and their activation levels surpass those of non-essential activators. In summary, our study unveils the widespread importance of enzymatic activators and suggests that feed-forward activation of conditional metabolic pathways through essential metabolites mediates metabolic plasticity.